Dinamika Tradisi Intelektual Melayu - Izzuddin, Muhammad Haidar; Afriansyah, Syafran; Nurmalina, Nurmalina (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
This article aims to determine the dynamics of the intellectual revival of the Malay world which includes the supporting factors for the intellectual revival of the Malay world, Malay intellectual figures and their works. This article is presented descriptively qualitatively using literature review techniques. The research results show that the formation of intellectual traditions in the Malay world is closely related to the process of Islamization of the archipelago. It is strongly suspected that the intellectual tradition was only formed during the sultanate, in the early days of the arrival and spread of Islam through trade activities and Islamic preaching. Furthermore, there was an increase in the intensity of relations between the Malay (Nusantara) community and Arab countries, especially Haromain. This happens with many people from the archipelago who perform the Hajj and who deliberately settle in Mecca or Medina to study there. These are the people who, after returning to the archipelago, became actors in the process of transmitting religious thought to the Muslim community of the archipelago.